2016
DOI: 10.1007/978-3-319-25474-6_9
|View full text |Cite
|
Sign up to set email alerts
|

Intelligibility for Binaural Speech with Discarded Low-SNR Speech Components

Abstract: Speech intelligibility in multitalker settings improves when the target speaker is spatially separated from the interfering speakers. A factor that may contribute to this improvement is the improved detectability of target-speech components due to binaural interaction in analogy to the Binaural Masking Level Difference (BMLD). This would allow listeners to hear target speech components within specific time-frequency intervals that have a negative SNR, similar to the improvement in the detectability of a tone i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 11 publications
3
18
0
Order By: Relevance
“…However, in the speech‐in‐speech condition, the difference in masking release between HRTF and ISE condition is small. This is consistent with the findings by Schoenmaker and Van De Par (). There are two possible reasons for this significant difference that were further investigated.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…However, in the speech‐in‐speech condition, the difference in masking release between HRTF and ISE condition is small. This is consistent with the findings by Schoenmaker and Van De Par (). There are two possible reasons for this significant difference that were further investigated.…”
Section: Discussionsupporting
confidence: 94%
“…According to Cooke (), a suitable criterion for considering a spectrotemporal unit as a glimpse lies in the range of −2 to −5 dB. A similar suggestion is made by Schoenmaker and Van De Par (). Their experiment showed that removing speech fragments up to a local SNR of −4 dB did not have a significant effect on the speech intelligibility.…”
Section: Discussionmentioning
confidence: 75%
“…To further investigate this question, this study tested the hypothesis that low signal‐to‐noise ratio target components do not contribute significantly to speech discrimination in a spatial multitalker condition. For this, we apply an auditory “glimpsing” model (Josupeit & Hohmann, ) to a speech intelligibility task within a multitalker scene with a manipulated target stimulus (Schoenmaker & van de Par, ).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies indicate that listeners mainly process “glimpses” of information to decode complex auditory scenes (Best et al ., ; Cooke, ; Josupeit & Hohmann, ; Schoenmaker & van de Par, ). Glimpses are defined as spectro‐temporal undisrupted pieces of information (Darwin, ), that is a glimpse contains the information from exactly one sound source.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation